Metode Pemberdayaan Keluarga Dalam Pijat Bayi untuk Peningkatan Kualitas Tidur Bayi - Dewi Sapta Wati; Wahyu Utami Ekasari (LPPM AN Nuur, 2022)
Background The quality of a baby's sleep is the quality of the physiological state that is obtained while the baby is sleeping, which restores the body's processes that occur when the baby wakes up with the right amount of sleep. Sleep plays a very big role for the development of the baby. However, about 25% of sleep disturbances occur in infants, thereby disrupting the quality of the baby's sleep. Purpose : The purpose of giving this baby massage is to provide knowledge and it is implemented for all mothers or families who have babies aged 3-12 months. Metode: The method used in this service is to use the family empowerment method by carrying out baby massage to mothers or families who have babies aged 3-12 months through interpersonal relationships at TPMB Amalia Temon. Results : The results of the dedication of the family empowerment method in carrying out baby massage at the age of 3-12 months can be seen from the results of the quality of baby sleep which has increased in as many as 15 baby who have had baby massage and the knowledge of the baby's family has also increased. Conclusion: The method of implementing infant massage is proven to improve sleep quality in infants aged 3-12 months at TPMB Amalia Temon